Analysis of Branding Strategy through Instagram with Storytelling in Creating Brand Image on Proud Project - Martinus, Handy; Chaniago, Fachmi (Humaniora, 2017)
The objectives of the article were to study the branding strategy of a new age media company through social media with storytelling, how it could be utilized in the building of brand image, and what were the special characteristics of storytelling in social media environment, especially Instagram. The study provided an overview of factors in the online content update from social media to elevate interaction and to maintain the relationship between the company and its audience. Also specifying the points on how the information looked desirable to the customer. The qualitative descriptive content analysis was conducted to investigate how a new age media company with Instagram as the platform, which products were intangible and used storytelling in the delivery utilizes and mixes both components. Data were obtained by conducting the in-depth interview with company’s representative, public relations practitioner, and a follower of the company’s Instagram account, which then analyzed through data reduction. The research suggests that storytelling combined with social media features potentially strengthens all dimensions of brand equity with the brand image as the focus, primarily due to its engaging content, its ability to enhance the formation of an emotional connection, and its capabilities in improving recall and recognition. Branding activities conducted by Proud through Instagram can be said to be effective, taking into account the six main factors in providing updates, namely vividness, interactivity, informational content, entertaining content, position and valence of comments. Storytelling plays a role in communicating the company's brand and value. In addition, storytelling is also a branding tool that becomes an element that uniquely unveils a company with a competitor.